2011
DOI: 10.1111/j.1365-2907.2011.00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Callosciurus squirrels: worldwide introductions, ecological impacts and recommendations to prevent the establishment of new invasive populations

Abstract: ABSTRACT1. Rodents are traded as pet species, a practice that frequently results in new introduced populations. This is particularly true for tree squirrels where often only a few founders can establish viable colonies. 2. Here we review the worldwide introductions, ecology and impacts of two tree squirrel species, Callosciurus erythraeus and C. finlaysonii, and discuss the elements of a strategy to reduce squirrel introductions and settlements. 3. C. erythraeus has established viable populations in Argentina,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 58 publications
(103 reference statements)
1
47
0
1
Order By: Relevance
“…Similarly, the introduction events listed by Bertolino and Lurz (2013) for redbellied squirrels in Japan also indicate the occurrence of 17 new introductions after a lag period of approximately 20 years, though we cannot discriminate between multiple introductions and translocations within the country. Table 1 Year of introduction and number of red-bellied squirrels released at nine sites located in the city of Buenos Aires, and the provinces of Buenos Aires and Santa Fé, Argentina (see Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, the introduction events listed by Bertolino and Lurz (2013) for redbellied squirrels in Japan also indicate the occurrence of 17 new introductions after a lag period of approximately 20 years, though we cannot discriminate between multiple introductions and translocations within the country. Table 1 Year of introduction and number of red-bellied squirrels released at nine sites located in the city of Buenos Aires, and the provinces of Buenos Aires and Santa Fé, Argentina (see Fig.…”
Section: Discussionmentioning
confidence: 98%
“…population has been reporded in Italy though taxonomic identification is still pending . In all countries of introduction, only one or two Callosciurus populations have been reported with the exception of Argentina and Japan where several invasion foci have been described Bertolino and Lurz 2013). Native habitat in Southeast Asia includes tropical and subtropical evergreen forests and also conifer forests, while various arboreal habitat types are inhabited by C. erythraeus in introduced ranges such as natural forests, fruit and timber plantations, and parks and gardens in rural and urbanised areas; its highly arboreal habits relates to nesting on trees and feeding on vegetable matter mainly obtained from trees and shrubs .…”
Section: Introductionmentioning
confidence: 97%
“…Long (2003) provides accounts of 337 mammal species moved around the world (around 6% of the global mammal fauna), but some of this number have been re-introduced rather than introduced, while other mammal species with known introductions (e.g. Callosciurus finlaysonii, Bertolino and Lurz 2013) are missing from the compilation. A recent study by Capellini et al (2015) identified 232 mammal species as having been introduced (c.4% of the total mammal species richness) based on data in Long (2003) and other sources.…”
Section: Introductionmentioning
confidence: 99%
“…Squirrels have an enormous invasive capacity, as demonstrated by Callosciurus erythraeus and Sciurus carolinensis , which are able to successfully colonise new areas from as few as 10 initial individuals, causing considerable environmental damage in the new areas and being extremely difficult to eradicate (Palmer et al. , Bertolino & Lurz ).…”
Section: Introductionmentioning
confidence: 99%